Influence Of Feedstocks In Biodiesel Production On Its Physico-Chemical Properties Of Product : A Review - Oberlin Sidjabat (Testing Center for Oil and Gas LEMIGAS, 2013)
Â Biodiesel is attracting increasing attention worldwide as a substituted petroleum diesel fuel or a blending component in transport sector. Biodiesel also become more attractive because of its environmental benefits and the fact that it is made from renewable resources. Biodiesel feedstock can be divided into four main categories: (i). Edible vegetable oi; (ii). Non-edible vegetable oil, (iii); Waste or used cooking oil; and (iv). Animal fats. There are two major factors to take into consideration when dealing with feedstock for biodiesel production i.e the source and composition. Biodiesel feedstocks have three main types of fatty acids as the main compounds that are present in a triglyceride: saturated (Cn:0), monounsaturated (Cn:1) and polyunsaturated (Cn:2,3). The overall biodiesel physicochemical properties are strongly influenced by the properties of individual fatty acid esters in biodiesel. Fatty acid composition varies for all biodiesel feedstocks that affected the product quality. Important fuel properties of biodiesel that are influenced by the fatty acid composition are viscosity, cetane number, heating/ calorific value, cloud point,and oxidation stability. Oxidation stability is one of the major issues influencing the use of biodiesel or FAME (fatty acid methyl ester), due to the nature of biodiesel, makes it more susceptible to oxidation or auto-oxidation during long-term storage than petroleum diesel fuel. The oxidation stability values of the biodiesel range from 0.4 hr (for the most unsaturated biodiesel, linseed) to 35.5 hr (for the most saturated one, coconut).